Pengaruh Kombinasi Biji Labu Kuning dan Jamur Merang dengan Pengikat Umbi Gembili Terhadap Kadar Proksimat dan Profil Asam Amino Daging Analog: The Effect of Combining Pumpkin Seeds and Straw Mushroom with Lesser Yam as a Binder on the Proximate and Amino Acid Profile of a Meat Analog - Mumtaz, Shabrina Olivia; Nasrullah, Nanang; Fauziyah, A'immatul (Amerta Nutrition, 2025)
Background: Dyslipidemia is a significant risk factor for cardiovascular disease. The high prevalence of dyslipidemia is caused by the habitual consumption of foods contain saturated fats, such as beef. Therefore, meat analog made from plant-based ingredients is a potential alternative due to its high protein content and low fat content, especially regarding saturated fats. Objectives: To determine the effect of pumpkin seeds and straw mushroom combination with lesser yam as a binder on proximate and amino acid profile of meat analog. Methods: This study used a completely randomized design with three formulations based on the proportions of pumpkin seed flour and straw mushroom flour, such as F1 (75%:25%), F2 (50%:50%), and F3 (25%:75%). Each formulation is added with 25 g lesser yam puree. Proximate analysis was conducted to determine moisture, ash, protein, fat, and carbohydrate, with analysis of amino acid profile of meat analog. Statistical analysis of the data was conducted using ANOVA and Duncan’s Multiple Range (DMRT) test. Results: The three formulations of meat analogue had moisture 42.19-42.29%, ash 2.81-4.34%, protein 15.50-16.90%, fat 3.86-14.08%, carbohydrate 24.01-33.98%, and total amino acids 11.97-14.60%. The results showed that the three formulations of pumpkin seed flour and straw mushroom flour significantly affected ash content (p-value=0.020), fat content (p-value<0.001), carbohydrate content (p-value=0.004), as well as the amino acids threonine (p-value=0.019) and lysine (p-value=0.036). Conclusions: The combination of pumpkin seed flour, straw mushroom flour, and lesser yam as a binder had a significant effect on the proximate and amino acid profile of the meat analog.